Subcellular location and photodynamic therapeutic effect of chlorin e6 in the human tongue squamous cell cancer Tca8113 cell line - LUO, WEI (Oncol Lett, 2015)
The present study aimed to investigate the distribution and photodynamic therapeutic effect of chlorin e6 (Ce6) in the human tongue squamous cell carcinoma Tca8113 cell line in vitro. The distribution of Ce6 in the Tca8113 cells was observed in situ combined with mitochondrial and lysosomal fluorescent probes. Next, 630-nm semiconductor laser irradiation was performed. The MTS colorimetric method was used to determine cell survival. Annexin V fluorescein isothiocyanate/propidium iodide (PI) double staining was used to detect early apoptosis following photodynamic therapy (PDT). The flow cytometer was used to analyze the DNA content subsequent to PI-staining. It was observed that Ce6 could combine with the cellular membrane following 30 min of incubation with the Tca8113 cells. As the length of incubation increased, Ce6 gradually entered the cells in a particular distribution and reached saturation by 3 h. Co-localization analysis demonstrated that Ce6 was more likely to be present in the mitochondria than in the lysosomes. The cells incubated with 5 μg/ml Ce6 for 24 h exhibited a low toxicity of 5%, however, following light irradiation, Ce6-PDT was able to kill the Tca8113 cells in vitro. The cell toxicity was positively correlated with Ce6 concentration and light dose, therefore, the effect of Ce6 was concentration/dose-dependent (P<0.01). The lower Ce6 concentrations and light doses could significantly induce apoptosis in the Tca8113 cells, while higher doses increased necrosis/percentage of dead cells. In summary, Ce6 saturated the Tca8113 cells following 3 h of incubation. Furthermore, Ce6-PDT effectively killed the cultured Tca8113 cells in vitro at a safe concentration. At a low concentration and light dose, Ce6 is more likely to induce cell apoptosis via the mitochondria than the lysosomes.